The Face of Women in Cases of Domestic Violence in Indonesia According to the Ethics of the Levinasian - Wiparlo, Valerianus; Endi, Yohanes (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This article focuses on the face of women in Levinasian face ethics. The author raises issues related to the increasing phenomenon of violence against women in Indonesia. This fact shows that women in Indonesia are still neglected. According to Levinasian face ethics, this paper intends to criticize the problems that occur from a philosophical point of view. The method of discussion of this paper is a critical analysis of cases of violence against women in the household in the light of Levinasian face ethics. Forms of violence against women in Indonesia are strongly influenced by a patriarchal culture that places the position and status of men above women. This cultural model opens up space for male superiority over women. The concept of Levinasian face ethics is an effective tool in minimizing acts of violence against women in the household. The author arrives at the finding that the root of the problem behind the rampant cases of domestic violence in Indonesia is the failure to understand the existence of women and weak law enforcement. Levinas' ethics of responsibility provide new treasures for understanding Indonesian society, namely that the existence of women is part of everyone's responsibility. A woman's face is how